2019
DOI: 10.1111/tbj.13507
|View full text |Cite
|
Sign up to set email alerts
|

Flat epithelial atypia on core needle biopsy does not always mandate excisional biopsy

Abstract: Flat Epithelia Atypia (FEA) is a proliferative lesion of the breast where cells demonstrate columnar change and cytologic atypia. This lesion has been identified as distinct from the classic atypical hyperplasias (AH). While many patients undergo excisional biopsy, management of FEA identified on core needle biopsy (CNB) is controversial, and the rate of associated ductal carcinoma in situ (DCIS) or invasive cancer is not well Weak 11 (15.7)Strong 14 (20.0)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The literature shows much lower rates of upgrade in pure FEA lesions that have radiological and pathological concordance. [35][36][37][38] We are limited by small sample size and may consider a more conservative approach to FEA if our future data becomes consistent with the literature.…”
Section: Discussionmentioning
confidence: 78%
“…The literature shows much lower rates of upgrade in pure FEA lesions that have radiological and pathological concordance. [35][36][37][38] We are limited by small sample size and may consider a more conservative approach to FEA if our future data becomes consistent with the literature.…”
Section: Discussionmentioning
confidence: 78%
“…Historically, excisional biopsy has been recommended after a core needle biopsy diagnosis of all high risk lesions. Recent data suggest that upgrade rates to carcinoma in situ or invasive carcinoma are 4-23% for lobular neoplasia [27,28], up to 29% for ADH [18], 3-5% for flat epithelial atypia [29,30], 2-6% for papilloma without atypia [31][32][33], and 2-28% for radial scar [34] [35]. Most of these studies found that…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…FEA is often seen in combination with other high-risk lesions and is suggested to be a precursor lesion to both ADH and carcinoma [ 38 , 39 ]. Srour et al found a statistically significant increase in UR for FEA with ADH (18.6%) compared to pure FEA alone (3.2%) [ 40 ]. This finding is supported by Liu et al who demonstrated that pure FEA had a zero rate of upstage to malignancy and the presence of concurrent ADH or RS with FEA had an increased UR [ 7 ].…”
Section: Discussionmentioning
confidence: 99%